Determinan Keputusan Pembelian Produk Makanan dan Minuman: Analisis Peran Sertifikasi Halal, Kualitas Produk, dan Harga di Rocket Chicken Cabang Yogyakarta - Muhammad Lucky P. (Al-Maqashid: Journal of Economics and Islamic Business, 2024)
The food and beverage industry in Indonesia has experienced rapid development, especially with increasing consumer awareness of halal products. This also drives up the demand for halal products, especially halal food and beverage products, which are the primary needs of Muslims. Therefore, this research aims to examine the influence of halal certification, product quality and price on purchasing decisions for food and beverage products at Rocket Chicken Yogyakarta Branch. In this research, Rocket Chicken is considered to be a very potential research object because it is one of the developing types of Micro, Small and Medium Enterprises (MSMEs) which operates in the culinary sector. The method used in this research is the Multiple Linear Regression model by taking 66 respondents with the help of data processing using Eviews 10 software. The results of this research prove that halal certification and price have a significant influence on food and beverage purchasing decisions at Rocket Chicken Branch Yogyakarta. Meanwhile, separately, only the product quality variable was not significant. Therefore, MSMEs at Rocket Chicken Yogyakarta Branch must obtain halal certification, pay attention to product quality and price to increase consumer purchasing power for their products.